The combined application of chemical and microbial fertilizers enhanced microbial diversity and improved soil fertility in the peanut rhizosphere within a sugarcane-peanut intercropping system - Wu, Haining; Qin, Jiayu; Li, Boyin; Huang, Zhipeng; Liao, Guoting; Tang, Xiumei; Li, Zhong; Xiong, Jun; Gao, Zhongkui; Jiang, Jing; Zhong, Ruichun; Han, Zhuqiang; et al. (Frontiers in Microbiology, 2026)
The decline in soil microecological balance and fertility caused by continuous cropping obstacles and excessive application of chemical fertilizers has become a critical bottleneck restricting the sustainable development of the peanut industry. However, intercropping can enhance resource utilization efficiency, and microbial fertilizers can improve soil properties and increase nutrient usability. Therefore, we evaluated the effects of six fertilization treatments [no fertilization (CK), 100% chemical fertilizer (T1), microbial fertilizer (T2), 100%chemical fertilizer+microbial fertilizer (T3), 80% chemical fertilizer+microbial fertilizer (T4) and 60% chemical fertilizer+microbial fertilizer (T5)] on chemical properties and microbial communities of the rhizosphere soil of intercropped peanuts. The results showed that compared with T1, the combined application of chemical and microbial fertilizers significantly increased soil organic matter content and alleviated soil acidification. Microbial analysis indicated that the T4 treatment had the highest Shannon diversity, which was significantly higher than T1, demonstrating its effectiveness in reversing the suppressive effect of chemical fertilizer alone on microbial diversity. Principal coordinate analysis and redundancy analysis further confirmed that fertilization significantly altered microbial community structure, with a clear separation between the combined application and chemical-fertilizer-alone treatments, forming a distinct microbial community. Specifically, the T4 treatment significantly increased the abundance of rhizobia. Under T4 treatment, the abundance of assimilatory nitrate reductase genes (such as nasB and NR) decreased, while that of narB, and nirA increased; simultaneously, the abundance of dissimilatory nitrate reductase and denitrification-specific genes significantly increased. Mantel test analysis revealed significant positive correlations between soil total nitrogen, available nitrogen content, microbial communities, and crop yield. In summary, the combined application of chemical and microbial fertilizers optimizes the soil microenvironment by synergistically enhancing soil fertility (increasing organic matter, regulating pH) and reshaping microbial community structure (increasing diversity, enriching beneficial bacteria). These findings can provide theoretical basis for the optimization of fertilization strategy in peanut intercropping system.